2003
DOI: 10.1124/jpet.103.056697
|View full text |Cite
|
Sign up to set email alerts
|

Methylnaltrexone Antagonizes Opioid-Mediated Enhancement of HIV Infection of Human Blood Mononuclear Phagocytes

Abstract: Opioid abuse has been postulated as a cofactor in the immunopathogenesis of human immunodeficiency virus (HIV) infection and AIDS. We and others have recently demonstrated that opioid enhances HIV infection of human macrophages through modulation of ␤-chemokines and the CCR5 receptor and that this effect is reversed by naltrexone, a tertiary opioid antagonist. Tertiary opioid antagonists cannot be used in opioiddependent patients because they precipitate withdrawal or reversal of analgesia. We determined wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 30 publications
1
39
0
1
Order By: Relevance
“…Opioids are widely prescribed and also abused drugs in the United States and all over the world. Several studies from different laboratories indicate that opioid use may promote HIV disease progression by enhancing HIV replication and infection (Peterson et al 1990;Schweitzer et al 1991;Suzuki et al 2002;Guo et al 2002;Li et al 2003;Ho et al 2003;Wang et al 2005). Opoids, especially morphine, has been shown to promote HIV replication in many cell types through various mechanisms which are described below.…”
Section: Effect Of Morphine On Anti-hiv Mirna Expression In Monocytesmentioning
confidence: 99%
“…Opioids are widely prescribed and also abused drugs in the United States and all over the world. Several studies from different laboratories indicate that opioid use may promote HIV disease progression by enhancing HIV replication and infection (Peterson et al 1990;Schweitzer et al 1991;Suzuki et al 2002;Guo et al 2002;Li et al 2003;Ho et al 2003;Wang et al 2005). Opoids, especially morphine, has been shown to promote HIV replication in many cell types through various mechanisms which are described below.…”
Section: Effect Of Morphine On Anti-hiv Mirna Expression In Monocytesmentioning
confidence: 99%
“…This replication has been proposed as an explanation for the increased infectivity described in HIV-positive patients receiving opiates. Clinically relevant doses of MNTX block opiate-induced increases in the CCR5 receptor, as well as viral replication and entry in this model system 41 , suggesting a potential therapeutic role in the clinical setting of HIV positive patients with AIDS pain or addiction. Recent in vitro data suggest that morphine in clinically relevant doses promotes angiogenesis, partly by transactivation of VEGF receptors, and that this opiate-induced endothelial cell migration and proliferation can be attenuated by MNTX 42,43 .…”
Section: Other Potential Uses Of Peripheral Opiate Antagonistsmentioning
confidence: 84%
“…Propôs-se que essa replicação explicaria aumento na infectividade descrita em pacientes HIV-positivos que recebem opióides. Doses clinicamente relevantes de MNTX bloqueiam o aumento dos receptores CCR5, assim como a replicação viral e sua entrada nesse novo modelo 41 , sugerindo uso potencial nos pacientes HIV-positivos com dor ou dependentes de drogas. Recentes dados in vitro sugerem que a morfina, em doses clinicamente relevantes, promove a angiogênese, parcialmente por meio da transativação dos receptores VEGF e que essa migração e proliferação de células endoteliais induzida pelos opióides podem ser atenuadas pela MNTX 42,43 .…”
Section: Outros Usos Potenciais Dos Antagonistas Periféricos Dos Opióunclassified
“…Research data have demonstrated the effects of opioids to be suppressive on phagocytic, natural killer, B and T cells, and several studies have suggested that these immunomodulatory effects might be mediated via mechanisms different from those responsible for analgesia [Wei et al, 2003]. Methylnaltrexone antagonized opioid-mediated enhancement of HIV infection of human blood mononuclear phagocytes [Ho et al, 2003]. If peripherally mediated immunosuppressive effects play a significant role in opioidinduced immunosuppression, the use of methylnaltrexone could potentially attenuate opioid-induced immunosuppression while preserving the beneficial analgesic effect.…”
Section: Treatment Of Opioid-induced Immunosuppressionmentioning
confidence: 98%